Pemanfaatan Limbah Media Tanam Jamur Tiram Putih (Pleurotus Ostreatus) sebagai Kompos dan Pengaruhnya terhadap Hasil Tanaman Okra (Abelmoschus esculentus (L.) Moench) - Jumrida Atini; Rahmi Zulhidiani; Tuti Heiriyani (Agroekotek View, 2018)
Waste baglog or media for planting mushroom is the rest of te mushroom cultivation process unused again, so tat it can be used as compost. one of the important role of compost is creating soil fertility. Both the nature of the physical, biological, and chemical properties of the soil. Utilization of waste as an oyster mushroom growing media compost in this study was applied to plant okra. This study used a Randomized Complete Design (RAL), single factor with 5 treatment rooms, 4 times repeat, so come by 20 units of the experiment. The treatment is a k0 : soil control, k2 : 10 kg soil +  500 g soil/compost baglog waste plant, k3 : 10 kg soil + 750 g soil/compost baglog waste plant and k4 : 10 kg soil + 1000 g/compost baglog waste plant. Research results show that compost waste white oyster mushroom cropping media gives influence to the time of the first harvest, the amount of fruits per plant, average fruit length and weight of fruits per plant. Awarding waste composting treatment media white Oyster Mushrooms cropping rate of 500 g/plant gives the best results for harvest time first, the average amount of fruit, fruit length and weight of fruit per plant